2014
DOI: 10.3329/jbayr.v2i1.20539
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foreign Aid in the Economic Development of Recipient Country

Abstract: No abstract available.DOI: http://dx.doi.org/10.3329/jbayr.v2i1.20539 Journal of the Bangladesh Association of Young Researchers (JBAYR): Vol.2(1), 2012 & 2013: 33-37

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 2 publications
1
17
1
Order By: Relevance
“…Although official development assistance flows have increased, their developmental impact is not directly tangible compared to remittances that flow directly to their beneficiaries, with potential impacts on health, education, small-scale businesses, and the real sector. Moreover, several previous studies note that official development assistance does not necessarily translate to high economic growth rates (Yiew and Lau 2018;Phiri 2017;Murshed and Khanaum 2014). Historically, official development assistance has been misappropriated at both state and nongovernmental levels (Elayah 2016;Kono and Montinola 2013;Bodomo 2013;Doucouliagos and Paldam 2011;Maipose 2000).…”
Section: Remittance Flows In Kenyamentioning
confidence: 99%
“…Although official development assistance flows have increased, their developmental impact is not directly tangible compared to remittances that flow directly to their beneficiaries, with potential impacts on health, education, small-scale businesses, and the real sector. Moreover, several previous studies note that official development assistance does not necessarily translate to high economic growth rates (Yiew and Lau 2018;Phiri 2017;Murshed and Khanaum 2014). Historically, official development assistance has been misappropriated at both state and nongovernmental levels (Elayah 2016;Kono and Montinola 2013;Bodomo 2013;Doucouliagos and Paldam 2011;Maipose 2000).…”
Section: Remittance Flows In Kenyamentioning
confidence: 99%
“…In fact, the concept behind the positive impact of aid on growth is that aid can fill both investment and resources gaps where its complement savings and increases investment and capital accumulation. Therefore, foreign aid has positive impacts only in those economies that have good fiscal, monetary and trade policies, Burnside and Dollar (2000), which means that good economic policy pre-requested for aid effectiveness, Murshed and Khanaum (2014). Basnet (2013) examined the role of foreign aid on savings and economic growth in South Asian countries by utilizing a simultaneous equation system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whilst the study found results which support the foreign aid-led growth hypothesis in Jordan, foreign aid and economic growth were found to have had no causality effect on each other in Egypt. A study by Murshed and Khanaum (2012) also found results which supported foreign aid-led growth hypothesis in the case of Bangladesh. Kargbo (2012) explored the impact of foreign aid on economic growth in Siera Leone using the Autoregressive Distributive Lag (ARDL) with data from 1970 to 2007.…”
Section: Impact Of Foreign Aid On Economic Growth -A Literature Reviewmentioning
confidence: 70%
“…Empirical studies which supported the foreign aid-led positive growth hypothesis were done by Adam (2013), Lof, Mekasha and Tarp, F. (2015), Mekasha and Tarp (2015), Hossain (2014), Murshed and Khanaum (2012), Al-Foul (2013), Kargbo (2012), Minoiu and Reddy (2009) and Moreira (2005), among others.…”
Section: Impact Of Foreign Aid On Economic Growth -A Literature Reviewmentioning
confidence: 98%